2023
DOI: 10.3390/cancers15133406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Substructures Exposure of DIBH-3DCRT, FB-HT, and FB-3DCRT in Hypofractionated Radiotherapy for Left-Sided Breast Cancer after Breast-Conserving Surgery: An In Silico Planning Study

Abstract: Left-sided breast cancer radiotherapy can lead to late cardiovascular complications, including ischemic events. To mitigate these risks, cardiac-sparing techniques such as deep-inspiration breath-hold (DIBH) and intensity-modulated radiotherapy (IMRT) have been developed. However, recent studies have shown that mean heart dose is not a sufficient dosimetric parameter for assessing cardiac exposure. In this study, we aimed to compare the radiation exposure to cardiac substructures for ten patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Subclinical LV dysfunction appeared 6 months after the radiotherapy, as reported by Walker et al [18]. Recent studies [20,21] have proved that the deep inspiration breath-hold technique effectively contributes to a dose-sparing effect on the heart and these two cardiac substructures compared with free breath. However, this technique is not widely applicable at present.…”
Section: Introductionmentioning
confidence: 72%
“…Subclinical LV dysfunction appeared 6 months after the radiotherapy, as reported by Walker et al [18]. Recent studies [20,21] have proved that the deep inspiration breath-hold technique effectively contributes to a dose-sparing effect on the heart and these two cardiac substructures compared with free breath. However, this technique is not widely applicable at present.…”
Section: Introductionmentioning
confidence: 72%
“…In the WBI only group the DIBH technique and prone positioning provided similar heart sparing but, in a few cases one over the other provided superior results. Eber et al, in a similar analysis found that although 3DCRT with DIBH benefited most patients, in 2/10 cases alternative solution was needed in order to meet the dose constraints [31] .…”
Section: Discussionmentioning
confidence: 99%